Pengaruh Profitabilitas, Likuiditas, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Zahro, Aniqotuz; Sijabat, Rauly; Nastiti, Prianka Ratri (Innovative: Journal Of Social Science Research, 2024)
This study departs from the problem of fluctuations in the value of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The problem of fluctuations in company value is of course caused by several factors. This research aims to determine the effect of profitability, liquidity, capital structure and company size on company value in manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population used in this research is all manufacturing companies listed on the IDX for the 2020-2022 period. With a sample of 64 companies and a research period of 3 years, the total sample was 192. The data analysis technique in this research used the multiple linear regression analysis method. The results of this research conclude that the variables profitability, liquidity and company size together have a significant effect on company value. And the capital structure variable does not have a significant effect on company value.